2023
DOI: 10.1007/s11695-023-06461-1
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Nutritional Outcomes in Single-Anastomosis Duodeno-Ileal Bypass with Sleeve Gastrectomy Patients: an Australian Experience

Abstract: Nutritional deficiencies following malabsorptive surgeries are a major concern. Purpose To present clinical-based, mid-term nutritional outcomes in single-anastomosis duodeno-ileal bypass with sleeve gastrectomy (SADI-S) patients using a nutritional supplement based on the American Society for Metabolic & Bariatric Surgery (ASMBS) guidelines. Setting Single private institute, Australia. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Furthermore, we found that vit A and vit E deficiencies were the most common nutrient deficiencies, with an incidence rate of 45.5 and 25.8%, respectively. Interestingly, Rao et al 39 reported that the nutrient deficiency rate was 0% after 4 years of SADI-S surgery. This may be because the postoperative follow-up rate was high and nutrients were monitored and supplemented in time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that vit A and vit E deficiencies were the most common nutrient deficiencies, with an incidence rate of 45.5 and 25.8%, respectively. Interestingly, Rao et al 39 reported that the nutrient deficiency rate was 0% after 4 years of SADI-S surgery. This may be because the postoperative follow-up rate was high and nutrients were monitored and supplemented in time.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have described malabsorption as the predominant complication following SADI-S and DS interventions, resulting in consequential malnutrition, with prevalence rates ranging from 2% to 18.5% [ 117 , 118 , 119 ]. However, recent studies have identified GERD as a post-procedural side effect following SADI-S and DS [ 120 , 121 , 122 , 123 , 124 ].…”
Section: Surgical Choicementioning
confidence: 99%